Crystal structure of (2-methyl-1-phenylsulfonyl-1H-indol-3-yl)(phenyl)methanone. (February 2015) - Umadevi, M.; Saravanan, V.; Yamuna, R.; Mohanakrishnan, A. K.; Chakkaravarthie, G.
No abstract available